2004
DOI: 10.1177/1043659604265119
|View full text |Cite
|
Sign up to set email alerts
|

Native American Nurse Leadership

Abstract: Native nurse leaders lead differently. Thus, a leadership curriculum suitable for Native nurses may lead to increased work productivity and therefore improved patient care for Native Americans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 18 publications
2
23
0
Order By: Relevance
“…The study found that Aboriginal participants preferred their coaches to embody less autocratic behaviour than did the non-Aboriginal participants, and that both Aboriginal athletes and coaches reported that having strong communal and kinship ties was of great importance. Malloy and Nilson's findings are similar to those of Nichols' (2004) in that both studies indicated that Aboriginal and non-Aboriginal people display different preferences for and ways of leading. Both studies highlighted the fact that leaders, regardless of their specific job description, need to have a strong connection to and support from their community.…”
Section: Literature Review Aquaticssupporting
confidence: 84%
See 2 more Smart Citations
“…The study found that Aboriginal participants preferred their coaches to embody less autocratic behaviour than did the non-Aboriginal participants, and that both Aboriginal athletes and coaches reported that having strong communal and kinship ties was of great importance. Malloy and Nilson's findings are similar to those of Nichols' (2004) in that both studies indicated that Aboriginal and non-Aboriginal people display different preferences for and ways of leading. Both studies highlighted the fact that leaders, regardless of their specific job description, need to have a strong connection to and support from their community.…”
Section: Literature Review Aquaticssupporting
confidence: 84%
“…In light of these research findings and the limited success that the NWTAP has had in attempting to develop local aquatics leaders, it is imperative that the leadership approaches used by lifeguards reflect the NWT's communities' cultures and values. Baron's (1995), Malloy and Nilson (1991) and Nichols' (2004) research represent three significant studies that indicate why it is crucial to understand the interplay between culture and leadership. Baron's research focused on cultural management and how it is an important aspect of leadership.…”
Section: Literature Review Aquaticsmentioning
confidence: 97%
See 1 more Smart Citation
“…Most recently, Nichols (2004) completed focus groups involving 67 Native and non-Native nurses. The purpose was to identify characteristics, wisdom, and skills essential in effective Native American nurse leaders.…”
Section: Minority Female Leadershipmentioning
confidence: 99%
“…In the Native world, leadership is not sought; rather it is given and then for a prescribed period of time or until a particular result is attained (2009). family bonding is believed to be of greater importance then personal status (Nichols, 2004).…”
mentioning
confidence: 99%